Institutional and Organizational Features of the Cross-Border Freight Traffic in the Conditions of Integration among Former Soviet States. Part 2 - Tsvetkov, Valery Anatolevich; Zoidov, Kobilzhon Khodzhievich; Medkov, Alexey Anatolevich; Ionicheva, Valentina Nikolaevna (Economy of Regions, 2015)
The article considers the technical, technological, institutional and organizational barriers of cross-border transportation of goods. The study uses an institutional approach as a methodological alternative to other approaches. The institutional and organizational problems of border crossing points arrangement, the consequences of the application of unified transport documents, the introduction of electronic communication forms are analyzed. Particular attention is paid to the analysis of demonstration actions, the daily practice of reducing the time of customs procedures and reducing the transaction costs of crossborder freight traffic. At the same time, it is specified that the way of effectiveness increase of cross-border transportation of goods is a simultaneous implementation of technical and institutional innovations. Emphasis is placed on identifying the institutional and organizational features of the international transportation of goods by road, in particular, the problems of the evolution of the customs duties guaranteed payment institute, the permission system in the implementation of cross-border goods traffic. It is especially specified that the state support of national businessmen demands the development of a mechanism providing a parity of the Russian and foreign carriers, at least in the field of freight hauling for the state needs with attraction of credit resources of banks with the state participation. It is emphasized that elimination of all informal (shadow) relations in this sphere has to become the first step on the way of improvement of the institutional environment of the international road haulage. The institutional characteristics of transportation of goods in certain areas, in particular, road haulage to China through Kazakhstan, and the challenges and prospects for the use and development of the Kaliningrad region transit potential are allocated. The institutional and organizational characteristics of multimodal transport development in cross-border traffic are showed. The findings of the study suggest that the development of cross-border transportation of goods and the transport and transit potential implementation in Eurasian Economic Union countries - can and should provide income for business entities, the budgets of all levels and the public, as well as become the locomotive of industrial and technological modernization as well as institutional and organizational evolution of economic systems and integration associations.